1. Oblicz wartość wyrażenia/

a) -y + 8x - z - 2x dla x = -2 , y= 6 , z = -3
b) -8y - 4z + x - y - 2z + 1 dla x = -0,5 ; y= -1 ; z = 2
c) 9y - (7y + x) + (6x - 7y) dla x = -2 , y = 3
d) ½abc - (4ab + 2abc) + (-bc + 5ab) dla a = -2 , b = ½ , c = -4

3

Odpowiedzi

2010-03-23T16:54:23+01:00
A). -y + 8x - z - 2x dla x = -2 , y= 6 , z = -3

-6+8x-(-3)-2x=
-2x+3-2x=
-4x+3=-1x .

chyba dobrze . Ale nie jestem pewna . Zrobiłam tylko ,,a,, ponieważ dalszych nie jestem pewna. ;d
2010-03-23T16:56:44+01:00
A)-y+8x-z-2x=-6+8*-2-(-3)-2*(-2)=-6-16+3+4=22+7=29
Najlepsza Odpowiedź!
2010-03-23T17:06:12+01:00
A) -6 + 8 * (-2) + 3 - 2 * (-2) = -6 - 16 + 3 + 4 = 17
b) -8 * (-1) - 4 * 2 + (-0,5) - (-1) - 2 * 2 +1 =8 - 8 - 0,5 + 1 - 4 + 1 = -2,5
c) 9 * 3 - [7 * 3 +(-2)] +[6 *(-2) - 7 * 3] = 27 - (21 -2)+(-12 - 21) = 27 - 19 - 33
d) 1/2 * (-2) * 1/2 * (-4) -[4 * (-2) * 1/2 + 2 * (-2) * 1/2 * (-4)] + [-1/2 * (-4) + 5 * (-2) * 1/2 = 2 - (-4 + 8 ) + (2 - 5 ) = 2 -4 - 3 = 5